Hybrid computational scheme for antenna human body interaction - Ramli, K. N.; Abd-Alhameed, R. A.; See, C. H.; Excell, P. S.; Noras, J. M. (2013)
A new hybrid method of moments (MoM)/finite-difference time-domain (FDTD), with a sub-gridded finite-difference timedomain (SGFDTD) approach is presented. The method overcomes the drawbacks of homogeneous MoM and FDTD simulations, and so permits accurate analysis of realistic applications. As a demonstration, it is applied to the short-range interaction between an inhomogeneous human body and a small UHF RFID antenna tag, operating at 900 MHz. Near-field and far-field performance for the antenna are assessed for different placements over the body. The cumulative distribution function of the radiation efficiency and the absorbed power are presented and analyzed. The algorithm has a five-fold speed advantage over fine-gridded FDTD.